Direct power control for VSC-HVDC systems: An application of the global tracking passivity-based PI approach (2019)
This paper proposes a direct power control (DPC) for a high-voltage direct-current system using voltage source converters (VSC-HVDC) by applying passivity-based control theory. This system allows doing an efficient and reliable integration of electrical network from renewable energy sources. The DPC model permits instantaneous control of the active and reactive power without employing the conventional inner-loop current regulator and the phase-locked loop, thus diminishing investment costs and increasing the reliability of the system. The proportional-integral passivity-based control (PI-PBC) is chosen to control the direct power model of the VSC-HVDC system since this system exhibits a port-Hamiltonian formulation in open-loop and as PI-PBC can exploit this formulation to design a PI controller, which guarantees asymptotically stable in closed-loop based on Lyapunov's theory. Passivity-based control is an active research subject in the control community which has gained a reputation of being a very theoretical subject. Nevertheless, it can have advantages from a practical point of view including an implementation similar to the conventional controls for power systems applications. The paper is oriented to the power & energy systems community, taking into account this practical approach. The proposed controller is assessed by simulations in a two-terminal VSC-HVDC system and compared with a PI direct power controller. Four simulation conditions using MATLAB/SIMULINK were conducted to verify the effectiveness of PI-PBC against a PI controller and a perturbation observer-based adaptive passive control under various operating conditions. © 2019 Elsevier Ltd